Rancang Bangun Sistem Informasi Perencanaan Dan Pengadaan Kebutuhan Bahan Baku Dengan Menggunakan Metode Lot For Lot Pada PT Bukit Baja Anugrah - Irawan, Sari Zetari; Widodo, Arifin Puji; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Bukit Baja Anugrah is a company in the manufacturing of pipes.As long as companies are experiencing delays in the fulfillment of customer orders. This is because in determining the order fulfillment time is still based on estimates and orders directly from the manager in the purchase of raw material requirements, so there is no recording in detail the structure of the product requirements and checking of raw materials is not done on a regular basis also resulted in a shortage or excess raw materials. Based on these problems, then made the information system planning raw material requirements by using Lot For Lot. In the raw material requirements planning system there are some processes, namely the process of receiving data MPS where the information obtained in the form of raw material needs and schedule pre-defined messages, the process of recording the initial raw material inventory and process MRP (Material Requirement Planning). In the process there is a process that MRP Netting, Lot Sizing, Offsetting and Exploding. Based on the information system created by the testing that has been done, then this information system can meet the needs of raw materials needed for the production process, especially in producing a raw material requirements planning as any raw materials that must be ordered, how much, and when the raw materials have to be ordered. And information systems have resulted in reports of raw material requirements planning, inventory status reports and reports planned purchase of raw materials.